Ima3x design and implementation of an integrated multimedia environment - Gomez, Ray Vincent D.
Today, the need for applications with rich media interactivity and high connectivity is growing as seen in the emergence of Rich Internet Applications (RIA) applications like iGoogle where users can easily personalize their workspace and intuitively interact with it. However, multimedia applications are difficult to develop due to lack of available media toolkit applications that addresses issues like media integration and synchronization. Existing toolkits either have sophisticated graphical user interface that requires a minimum knowledge of media authoring or proficiency in a complex scripting language. Some of them are also not meant to ported to other platforms. This project introduces an integrated multimedia environment ? iMA3X system ? that allows users to create an electronic datascreen easily. The iMA3X Toolkit handles different media formats such as image, video, audio, and text and allows new formats to be added. Its user-friendly interface (UI) allows even untrained users to easily customize the layout and perform minor adjustments to the datascreen. It retrieves online information through RSS feeds such as news updates and displays them as a ticker. The iMA3X Builder allows the user to create an executable that displays the customized workspace into a full-screen datascreen. The design is implemented in Adobe Flex framework, executed in Adobe Integrated Runtime (AIR) environment and evaluated by different users to assess its UI usability.